Improving the interaction of small and medium-sized enterprises with banks in the process of credit interrelations - HUTSAL, Ihor (Scientific journal «World of Finance», 2019)
Introduction. The article outlines the directions of interaction of SMEs with banks, attention is focused on mutually beneficial cooperation of entities market economy because of the interdependence of their relationship. It is confirmed that the interaction between SMEs and banks in the process of financial intermediation is carried out by mutual influence that happens within the existing communications and is accompanied by the exchange of resources and their obligations based on operational needs and financial capabilities and economic feasibility.Purpose. For effective collaboration and interaction between SMEs and banks it is necessary to implement the motivational principles at the regional level through the development of market infrastructure. On the first phase should be solved the problem of matching supply and demand of credit resources, mainly through refinancing of banks according to the needs of SMEs.Results. The next phase requires implementation of customer-oriented strategy of SMEs’ needs on the part of banks by systematization and standardization of banking products. Ideal variants for meeting the needs of SME banking products – are special loan programs, which are clustered approaches indeed.Conclusion. It is proved that the interaction of SMEs and banks is carried out by mutual influence between them in the process of sharing resources and obligations within financial contracts. Such interaction is based on operational needs and financial possibilities, economic expediency.